A ANALISIS KADAR SULFAT SO42- PADA AIR MINUM YANG MENGANDUNG TAWAS DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-Vis - Darni Darni Darni; Rahmadani Rahmadani; Tuti Alawiyah (LPPM Universitas Sari Mulia, 2020)
ABSTRACT Background Alum is an aluminum sulfate compound consisting of sulfate double salts which has metal ions. Has the chemical formula [Al2(SO4)3.18H2O]. The maximum level of sulfate that is allowed to be contained in drinking water is regulated by the Republic of Indonesia Regulation No.492/Menkes/Per/IV/2010 of 250 mg/l. Objective To find out sulfate levels in drinking water samples consumed by Lok Buntar Village community. Method The study used an Analytical Observational Prospective Cohort Design. The population of the Lok Buntar Village research population is alum use as a water purifier that is used as drinking water. The research sample is boiled drinking water containing sulfate (alum) in Lok Buntar Village. Taken by purposive sampling. Data analysis using linear regression to determine levels. Results SO42- sulfate levels at volume of 150 L obtained 53.184 mg/l, at a volume of 100 L that is 42.162 mg/l, at a volume of 50 L obtained levels of 40.266 mg/. Ha â‰ 0 there are SO42- levels in drinking water at the sampling point at volumes of 150 L, 100 L and 50 L. Conclusion: The presence of SO42- sulfate levels at the sampling point at a volume of 150 L is 53.184 mg/l, 100 L is 42.162 mg/l and 50 L is 40.266 mg/l. Keywords Drinking Water, SO42- Sulfate Levels, UV-Vis Spectrophotometry.